Annual short-burst mass anthelmintic administration reduces tuberculosis severity but not prevalence in a wildlife reservoir - Lello, Joanne; Gassó, Diana; Gonçalves, Pilar; Risco, David; García, Waldo L.; Segalés, Joaquim; Garrido-Amaro, Cristina; Mentaberre, Gregorio; Torres-Blas, Irene; Velarde, Roser; López-Olvera, Jorge R.; Fernández-Llario, Pedro; et al. (Frontiers in Ecology and Evolution, 2023)
Tuberculosis (TB), caused by the Mycobacterium tuberculosis complex (MTC), is one of the three mostan important diseases in both human and animal systems. Helminths are commonly found in coinfection with MTC and TB is often exacerbated in such coinfections. Long-term anthelmintic administration, to control helminths, can improve a host's ability to control MTC infection. Mass drug administration programmes, in which anthelmintics are given only once or twice a year, leaving periods where helminth reinfection can occur, are common in both human and domestic animal populations.To date, the effect of such intermittent control programmes on MTC infection and severity has not been explored. Here we investigate the consequences of a ten-day, annual, mass ivermectin administration on TB prevalence and severity in free-ranging juvenile and yearling (<2 years) wild boar (Sus scrofa). This single annual anthelmintic treatment administered over six years reduced TB severity. Further, the proportion of wild boar with severe TB continued to decrease with successive treatments. TB prevalence, however, did not decrease significantly over the course of the study. While ivermectin has direct anti-mycobacterial effects in vitro, the lack of reduction in prevalence suggests that ivermectin decreases TB severity in wild boar through mechanisms other than a reduction in mycobacterial load. Disruption of the helminth community and subsequent modification or enhancement of the host immune response is a potential mechanism. Future work should examine the consequences of annual anthelmintic drug administration on helminth community composition and structure and on the host immunological responses through time.